Participation of Beauveria Bassiana Production Using Agricultural Waste in Baan Ton Mapraw Soong Community, Songkhla Province - Petlamul, Wanida; Mahamad, Kuntapon (Area Based Development Research Journal, 2020)
The use of entomopathogenic fungi is one of the biological methods for promoting organic agriculture to reduce insecticide use. The objective of this research is to present Beauveria bassiana production using agricultural waste (AW) by the participation in Baan Ton Mapraw Soong community, Hatyai district, Songkhla province. The 20 farmers participating in the project are selected by a purposive sampling method. The processes include: 1) design and development of engineering-technology-based B. bassiana production system, which contains local bio-chamber, local autoclave, and automatic control system incubator, and 2) transferring knowledge of B. bassiana production from AW. The produced B. bassiana presents the spore number in the range of 106-108 conidia/milliliter. After applying B. bassiana with crops of Cantonese vegetables, yard-long bean, eggplant, morning glory, and Chinese cabbage, it is found that farmers can reduce their insecticide cost by 7.72-16.92%. The community participation model indicates various important stakeholders - a gathering of community leaders and potential farmers, an operating committee for production planning and B. bassiana application, and a strong collaborative network. The network involves 1) Local government organization to coordinate and promote agricultural products, 2) School as a source of learning for agriculture and environment, 3) Public Health Office as the agency to promote the consumption of healthy agricultural products, and 4) Vendors for intermediary distributing agricultural products. These results indicate that farmers advance their knowledge and develop their practical skills as well as are able to disseminate the knowledge or extend it in a larger scale. In conclusion, the collaborative network promotes and upgrades sustainable agricultural products with a firm root in the local economy, society, and environment.